Implementasi Program Bantuan Pangan Non Tunai Oleh Pendamping Keluarga Harapan Di Desa Sidaharja Kecamatan Pamarican Kabupaten Ciamis - Mita Aprilia; R. Rindu Garvera; Asep Nurdin Rosihan Anwar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research is motivated by the persistence of poverty in rural areas, prompting the government to launch a non-cash food assistance program as a form of social assistance for underprivileged families. The purpose of this study is to determine the implementation of the non-cash food assistance program by Family Hope Facilitators in Sidaharja Village, Pamarican District, Ciamis Regency. This study used a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The results indicate that the implementation of the Non-Cash Food Assistance Program by Family Hope Facilitators in Sidaharja Village, Pamarican District, Ciamis Regency has not been running optimally. This is indicated by several dimensions and indicators, particularly in the communication dimension, where there are obstacles in the provision of assistance that are not properly targeted to beneficiary families.